Fiscal federalism in crisis: lessons for Europe from the US - Zsolt Darvas (Bruegel, 2010)
Drawing comparisons between the fiscal architecture and situation in the US and the European Union, Bruegel Research Fellow Zsolt Darvas answers three questions in this Policy Contribution- Why has the euro been hit so hard? How would a more federal European fiscal union closer to the US model have helped? How do the euro area's fiscal architecture reform plans stand up in light of the US example? He concludes that a higher level of fiscal federation is not inevitable for the viability of the euro area, but current European fiscal reform proposals carry political risk and their implementation could be deficient or lack credibility. Introduction of a Eurobond covering up to 60 percent of member states' GDP would be a much more preferable solution.
Keywords: 330; Finanzföderalismus; Euro-Anleihe; Finanzmarktkrise; Eurozone; EU-Staaten; USA